Efforts to Improve Scientific Literacy Through Ethnoscience-Based Learning in Science Learning - Nurul Hidayah Nasution; Irda Wahidah Nasution (Penerbit Widina, Widina Media Utama, 2026)
Education in the 21st century demands students to possess critical and creative thinking skills, effective communication abilities, and collaborative competencies in the learning process. Science education plays a strategic role in integrating literacy skills with scientific understanding, as it examines natural phenomena through systematic scientific methods. In science learning, students are expected not only to master scientific concepts but also to develop problem-solving skills, critical thinking, and the ability to apply knowledge in real-life contexts. However, scientific literacy that integrates cultural perspectives remains insufficiently emphasized in the Indonesian education curriculum. Incorporating scientific literacy through cultural contexts is essential as an effort to strengthen students’ sense of patriotism and appreciation of national cultural identity. This article employs a literature review method by analyzing and synthesizing findings from national research articles related to ethnoscience-based learning and scientific literacy. A meta-analysis approach was conducted by tracing relevant publications indexed in Google Scholar and Portal Garuda from 2023 to 2025. The selected articles were analyzed descriptively to identify patterns, key findings, and implications regarding the effectiveness of ethnoscience-based learning in enhancing students’ scientific literacy. The results of the analysis indicate that ethnoscience-based learning contributes positively to students’ attitudes toward science, conceptual understanding, and scientific reasoning skills. This approach emphasizes integrated understanding by connecting scientific concepts with local culture, traditional knowledge, and the surrounding environment, thereby making learning more contextual and meaningful. Furthermore, the appropriate use of learning media aligned with instructional objectives, learning materials, and students’ characteristics is crucial in supporting the successful implementation of ethnoscience-based learning. Overall, ethnoscience-based learning is a promising approach to improving scientific literacy while preserving and valuing local cultural wisdom.ABSTRAKPendidikan abad ke-21 menuntut peserta didik memiliki keterampilan berpikir kritis dan kreatif, kemampuan berkomunikasi secara efektif, serta keterampilan bekerja sama dalam proses pembelajaran. Pembelajaran IPA memiliki peran strategis dalam mengintegrasikan kemampuan literasi dengan pemahaman sains, karena IPA mempelajari fenomena alam melalui metode ilmiah yang sistematis. Dalam pembelajaran IPA, peserta didik tidak hanya dituntut memahami konsep, tetapi juga mengembangkan kemampuan pemecahan masalah, berpikir kritis, dan penerapan pengetahuan dalam kehidupan sehari-hari. Namun demikian, literasi sains yang terintegrasi dengan aspek budaya masih jarang mendapat perhatian dalam kurikulum pendidikan di Indonesia. Padahal, penerapan literasi sains berbasis budaya penting sebagai upaya menumbuhkan rasa cinta tanah air melalui penguatan identitas budaya bangsa. Artikel ini menggunakan metode kajian pustaka dengan menganalisis dan menelaah artikel penelitian nasional yang relevan dengan pembelajaran berbasis etnosains dan literasi sains. Penelusuran artikel dilakukan melalui Google Scholar dan Portal Garuda pada rentang tahun 2023–2025. Data dianalisis menggunakan metode deskriptif untuk menggambarkan temuan penelitian, kemudian disintesis guna memperoleh kesimpulan mengenai peran pembelajaran berbasis etnosains dalam meningkatkan literasi sains. Hasil kajian menunjukkan bahwa pembelajaran berbasis etnosains mampu mengembangkan sikap positif terhadap sains, meningkatkan pemahaman konsep, serta memperkuat kemampuan berpikir ilmiah peserta didik. Pendekatan ini menekankan pemahaman terpadu dengan mengaitkan konsep sains dengan budaya lokal, pengetahuan tradisional, dan lingkungan sekitar sehingga pembelajaran menjadi lebih kontekstual dan bermakna. Selain itu, pemilihan media pembelajaran yang sesuai dengan tujuan, materi, dan karakteristik peserta didik menjadi faktor penting dalam mendukung efektivitas pembelajaran berbasis etnosains.